The Impact of Agricultural Extension Policies on Nutritional Outcomes: The Case of NAADs in Uganda - Chumo, Chepchumba (The African Economic Research Consortium, 2021)
Agriculture is a very important pillar in most African countries’ development strategies. East African countries have been upbeat on agricultural issues because all of them are members of the Comprehensive Africa Agriculture Development Programme (CAADP). This initiative has set the goal of a minimum of 6% of agricultural annual growth and 10% of every government spending in agriculture, which should then translate to nutrition security, a key item in the Sustainable Development Goals (SDGs). Reducing and ultimately eradicating malnutrition and hunger is mandatory in achieving any meaningful economic growth as most economic activities are fully dependent on healthy populations that provide the required workforce.